Accidents in agriculture in the Kraśnik district in 2011 compared to the Agricultural Social Insurance Fund (KRUS) data - Kos, Marek; Gomuła, Henryk; Drop, Bartłomiej (Polish Journal of Public Health, 2013)
Introduction. Injuries are one of the major problems of modern medicine, especially for the employees of the agricultural sector, due to the nature and conditions of work. Given the dominance of this sector of employment in Kraśnik district, this problem requires a careful analysis to determine the strategy for the prevention of injuries in agriculture and the removal of their consequences. Aim. The purpose of this paper is to characterize injuries of farmers in the Kraśnik district, their correlation with the seasonal intensity of work and to determine age groups and gender of those most ulnerable . Material and methods. The representative group consisted of 102 patients residing in the Kraśnik district, treated for injuries incurred during the work related to agriculture and selected from 912 patients treated in the Department of Trauma Surgery Unit of Orthopedic Subdivision of Health Care Unit (SPZOZ) in Kraśnik in 2011. Results. The analyzed material shows that the most common in the Kraśnik district are injuries of the upper limbs of the male population of farmers aged 40-49 years. These injuries occur more often in winter than in summer, usually in the afternoon. Apart from the accident rate, which for the Lublin province is higher than for other areas of Poland, this data does not significantly deviate from the Agricultural Social Insurance Fund (KRUS) data. However, this research reveals a population of children and young people aged up to 18 years representing 9.8% of all hospitalized due to injuries on the farm, which, due to the nature, are not taken into account in Agricultural Social Insurance Fund data, although it is an important social issue. Conclusions. Injuries in agriculture in Kraśnik district usually occur amongst middle-aged men (40-49 years). Injuries that occur while working in agriculture are usually injuries of the upper and lower limbs and are characterized by seasonal occurrence and usually occur in the winter and the summer months.